FAKTOR-FAKTOR PERILAKU PICKY EATER PADA ANAK: SCOOPING REVIEW - Anggreni, Dewa Ayu Bella Riska; Kusumaningtiyas, Dwi Prima Hanis; Dwijayanto, I Made Rio (Universitas Prima Indonesia, 2023)
Picky eater or better known as having difficulty eating, is a problem in food harvesting in an effort to meet nutritional intake in children. Based on research in several countries, it can be seen that the prevalence of picky eaters or difficulty eating in children is quite high. Research in the USA reports that 50% of 3,022 toddlers have difficulty eating and around 20% -60% of parents say that their toddlers eat not optimally. In London, 17% of children have a low appetite, while another 12% are picky eaters. The prevalence of picky eaters in Singapore with frequent classification was 49.6% of 407 respondents, the Jakarta area was 46.9%, 59.5% of children aged 6-60 months in Depok, and 82% of children aged 3-6 years in Bekasi Regency is experiencing picky eater. Purpose: to be able to find out the factors that cause picky eater behavior. Literature review uses secondary data taken from Google Scholar. The results of this literature review present articles regarding the factors that cause picky eaters. There are factors that cause picky eaters. One of them is mother's knowledge about nutrition with picky eater behavior.